Oxygen depletion recorded in upper waters of the glacial Southern Ocean - Zunli Lu (Nature Portfolio, 2016)
Oxygen depletion in the ocean interior may be closely linked to atmospheric CO2level, yet robust proxies are scarce. Here, using foraminiferal I/Ca as a proxy for oxygenation changes, the authors show that oxygen depletion in the upper waters of the high latitude Southern Ocean occurred during glacials.